Levetiracetam attenuates diabetes-associated cognitive impairment and microglia polarization by suppressing neuroinflammation - Zhang, Yun-yun; Wang, Lu; Guo, Hua; Han, Ting-ting; Chang, Yan-hua; Cui, Xiao-chuan (Frontiers in Pharmacology, 2023)
Cognitive impairment is a common complication and comorbidity of diabetes. However, the underlying mechanisms of diabetes-associated cognitive dysfunction are currently unclear. Moreover, there is a lack of strong evidence for treatments of diabetes- associated cognitive impairment in addition to controlling blood glucose. Here, diabetic rats were established by intraperitoneal injection of one dose of streptozotocin (60 mg/kg). Polarization transitions of microglia were induced by high glucose treatment in BV2 cells. Levetiracetam was orally administered to rats 72 h after streptozotocin injection for 12 weeks. The Morris water maze test was used to assess the cognitive function of the rats. Hematoxylin-eosin staining and immuno- histochemical analyses were performed to evaluate the brain pathology. The levels of TNF-α, IL-1β, and IL-6 were measured by an ELISA. The mRNA expression of inflammatory factors was further measured by qRT-PCR. The expression of MAPK and NF-κB signaling pathways proteins was detected by Western Blotting. The in vivo experiment demonstrated that levetiracetam improved rat cognitive function and hippocampus morphology, and the effect was more evident in the high-dose levetiracetam group. Microglia activation in the hippocampus was inhibited by levetiracetam treatment for 12 weeks. Serum levels of TNF-α, IL-1β, and IL-6 were reduced in the LEV-L and LEV-H groups, and IL-1β level was obviously reduced in the LEV-H group. In vitro, we found that levetiracetam 50 µM attenuated microglial polarization by increasing IL-10 level and decreasing IL-1β and TNF-α levels. Moreover, levetiracetam 50 µM increased and decreased the proportion of CD206+/ Iba1+ and iNOS+/Iba1+cells, respectively. Western blot analysis illustrated that LEV 50 µM downregulated the expression of MyD88 and TRAF6, and phosphorylation of TAK1, JNK, p38, and NF-κB p65. The effect of levetiracetam on the anti-polarization and expression of p-JNK and p-NF-κB p65 were eliminated by anisomycin (p38 and JNK activators). Together, our data suggest that levetiracetam attenuates streptozotocin- induced cognitive impairment by suppressing microglia activation. The in vitro findings also indicate that the levetiracetam inhibited the polarization of microglia via the JNK/MAPK/NF-κB signaling pathway.